Razlike v sodelovanju vzgojiteljev in staršev v okoljih z različnim socialno-ekonomskim statusom - Janžekovič Žmauc, Irena (Revija za elementarno izobraževanje, 2014)
Preschool education is not possible without the cooperation of the parents, because it represents a complement to family education. Socio-economic status of parents is one of the factors that affect the cooperation of preschool teachers and parents. The empirical study checked whether there are differences in the types and frequency of participation of preschool teachers and parents in the areas of two Slovenian statistical regions that differ in the socio-economic status. We found that preschool teachers in the environment with lower socio-economic status more often cooperate with parents in some formal and informal modes of cooperation than they do in the environment with higher socio-economic status.
Keywords: cooperation with parents; predšolska vzgoja; predšolski otroci; formal forms; informal forms, frequency of participation, socio-economic status of the environment; otroški vrtci; frequency of participation, socio-economic status of the environment; starši; socio-economic status of the environment; sodelovanje